Problems and Solutions in Chinese Basic Education - Xu, Yunfei (Journal of Education and Educational Technologies, 2023)
The study combs the achievements and existing problems of Chinese basic education development since the reform and opening up 40 years ago, and based on the theory of educational equity and equalization of public services, and compares the data released by the Ministry of Education in 2012 and 2021, it can be found that compulsory education the number of schools in the stage has been reduced, the enrollment and enrollment have increased to a certain extent, and the nine-year compulsory education consolidation rate has increased; the gross enrollment rate in high school has increased by 6.4%, full-time teachers have increased significantly, and the student-teacher ratio has been further optimized. This study found that the key issues of Chinese basic education are mainly in the aspects of education evaluation, teacher team construction, and digital empowerment education. Therefore, it is proposed to implement the evaluation content of basic education under the guidance of the "Overall Plan for Deepening Educational Evaluation Reform in the New Era"; Guided by the policy of public-funded normal students, improve the quality of teacher supply; take the digitalization of education as the guide, to accelerate the development of basic education and other policy recommendations, so as to promote the development of basic education in China.